Absence of juvenile effects confirmed in stable carbon and oxygen isotopes of european larch trees - Kilroy, Eleanor (Acta silvae et ligni, 2016)
We report carbon and oxygen isotope ratios measured from the pith at breast height (ca. 1.2m) of three European larch (Larix decidua Mill.) trees growing in a mixed wood in West Wales, UK. The non-climatic rising trend of carbon isotope ratios reported for other species during early (juvenile) growth is not present and neither isotope shows significant trends as the tree matures. Results from the first ten rings are not significantly different from the next two sets of ten rings. Absence of a juvenile effect in carbon isotopes of European larch has been reported from trees growing in a low density stand in France and attributed to an absence of shading and no use of respired carbon dioxide. This site, in contrast, is densely wooded and the dominant oaks predate the larch trees, suggesting that juvenile effects, when present, may instead be caused by changes in hydraulic conductivity. More research is needed on juvenile effects as the current practice of avoiding juvenile wood is restricting the potential of stable isotope analysis of tree rings for dendroclimatology and plant physiology.
Keywords: macesen; branike; rast; stabilni izotopi; juvenilni efekt